The Use of Direct Oral Anticoagulants for Prevention of Stroke and Systemic Embolic Events in East Asian Patients with Nonvalvular Atrial Fibrillation - Chang-Sheng Ma (Cardiovascular Innovations and Applications, 2018)
As patients in East Asia age, the prevalence of age-related and chronic disease, including nonvalvular atrial fibrillation, may increase. Although warfarin has been the primary choice of anticoagulant for the prevention of stroke and systemic embolic events, the use of direct oral anticoagulants (DOACs) is increasing. DOACs do not require monitoring of the international normalized ratio to determine the optimal dose, and have a lower potential for food and drug interactions, improved benefit-risk profiles, and a quicker onset and offset of action relative to warfarin. The pivotal phase 3 trials for each of the DOACs – dabigatran, rivaroxaban, apixaban, and edoxaban – included at least some East Asian patients. Additionally, several clinical trials were conducted specifically for East Asian patients. This review discusses patterns and predictors of anticoagulant use in East Asian patients with nonvalvular atrial fibrillation, summarizes current guideline recommendations for East Asian patients, details the primary results demonstrating the safety and efficacy of DOACs in East Asian patients relative to non–East Asian patients, provides real-world data supporting the phase 3 testing results, and addresses the clinical profile of DOACs in East Asian populations, including patients at high risk of stroke.